Temperature Deformation of Cylinder-Piston Group Parts of Uprated Diesels and Gas Engines for Kamaz Vehicles - A. Nikitin, D.; D. Mezhetsky, G.; S. Denisov, A.; N. Baskov, V.; V. Chekmarev, V. (International Journal of Engineering and Technology, 2018)
The paper describes the effect of temperature on the deformation of cylinder-piston group parts of uprated diesel engines and gas engines of the KAMAZ family. Based on the 3-D model with the use of the finite element method, the hypothesis proposed by the authors on the necessity to change a number of limiting dimensions of the cylinder-piston group parts is confirmed. The purpose is to ensure their performance at elevated temperatures in comparison with the basic engines. It is also shown that the design model is adequate to the actual operating conditions of the engines under consideration.Â Â